131 PARATHYROIDECTOMY PREVENTS CALCIUM LOADING AND OXIDATIVE STRESS IN RATS WITH ALDOSTERONISM. (1st January 2006) - Vidal, A.; Sun, Y.; Bhattacharya, S. K.; Ahokas, R. A.; Gerling, I. C.; Weber, K. T.
Abstract : Purpose: Congestive heart failure (CHF) is accompanied by a systemic illness that includes oxidative stress in diverse tissues and bone wasting. To simulate one aspect of the neurohormonal activation seen in the CHF syndrome, aldosterone (ALDO, 0.75 μg/h) is administered by implanted minipump to uninephrectomized rats to raise plasma ALDO levels to those found in human CHF. Aldosteronism is associated with hypercalciuria, hypermagnesuria, and fecal loss of these divalent cations; each contribute to a fall in plasma-ionized [Ca 2+ ]o and [Mg 2+ ]o . Despite these losses of Ca 2+ and a decline in its extracellular concentration, total intracellular and cytosolic-free [Ca 2+ ]i are increased, together with an induction of oxidative stress. This includes peripheral blood mononuclear cells (PBMC), heart, and skeletal muscle. The resulting elevation in plasma parathyroid hormone (PTH) and reduction in bone mineral density seen with ALDO/1% NaCl treatment (ALDOST) led us to hypothesize that Ca 2+ loading and altered redox state are due to secondary hyperparathyroidism (SHPT). Methods: Accordingly, in rats receiving ALDOST, without or with a Ca 2+ -supplemented diet and/or parathyroidectomy (PTx), we monitored urinary Ca 2+ and Mg 2+ excretion; plasma [Ca 2+ ]o, [Mg 2+ ]o and PTH; PBMC [Ca 2+ ]i and H2 O2 production, and plasma a1 -antiproteinase activity, an inverse correlate of oxidative stress; total Ca 2+ and Mg 2+ in bone, myocardium, and rectus femoris; and gp91 phox labeling in the heart as a marker of NADPH oxidase activation. Results: We found the hypercalciuria, hypermagnesuria, and decline (p < .05) in plasma [Ca 2+ ]o and [Mg 2+ ]o that occur with ALDOST were not altered by a Ca 2+ -supplemented diet alone or with PTx plus this diet; the rise (p < .05) in plasma PTH seen with ALDOST, with or without the Ca 2+ -supplemented diet, was prevented by PTx; increased (p < .05) PBMC [Ca 2+ ]i and H2 O2 production, increased total Ca 2+ in heart and skeletal muscle, and fall in bone Ca 2+ and Mg 2+ and plasma a1 -antiproteinase activity present with ALDOST were each abrogated (p < .05) by PTx; and gp91phox activation, found in inflammatory cells invading the perivascular space of intramural coronary arteries of the right and left ventricles at 4 wks ALDOST was attenuated by PTx. Conclusions: Aldosteronism is accompanied by SHPT with PTH-mediated Ca 2+ overload of PBMC, heart, and skeletal muscle leading to the induction of oxidative stress. SHPT plays a permissive role in the genesis of the proinflammatory vascular phenotype in aldosteronism.